PERAN ORANG TUA DAN GURU DALAM PEMBENTUKAN KARAKTER SPIRITUAL ANAK USIA DINI DI TK NEGERI PEMBINA KOTA TIMUR KOTA GORONTALO - Nurhayati Tine; Sri Rahayu Bakari; Rapi Us. Djuko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to investigate the roles of parents and teachers in shaping the spiritual character of early childhood students at TK (Public Kindergarten) Pembina, Kota Timur Subdustrict, Gorontalo City. This This Study utilized a descriptive qualitative method focusing on the roles of parents and teachers in fostering the spiritual character of early childhood. The subjects comprised 6 parents and 3 teachers from class B at TK (Public Kindergarten) Pembina, Kota Timur Subdustrict, Gorontalo City. The objective is to describe their roles in shaping the spiritual character of early childhood. Data collection techniques employed were observation, interviews, and documentation. The findings illustrate that parents play a significant role in shaping the spiritual character of early childhood through five indicators: (1)Teaching honesty, acknowledging mistakes when made, (2)Teaching courag, fostering bravery and resilience againts fear, (3)Teaching Simplicity:promoting frugal living and moderation, (4)Teaching Responsibility:instilling completion of tasks, and (5)Teaching discipline:establishing simple rules. Additionally, the study highlights that teachers contribute to forming the spiritual character of early childhood throug seven indicators: (1)Educator:instilling norms and ethical values, (2)Instructor:imparting knowledge and insights, (3)Mentor:guiding and directing, (4)Advisor:providing advice and solutions in problem-solving, (5)Coach: training accompanied by praise, (6)ModelExemplar:demonstrating behavior directly, and (7)Motivator:providing encouragement, based on the findings at TK (Public Kindergarten) Pembina, Kota Timur Subdustrict, Gorontalo City, the role of parents in shaping the spiritual character of early childhood is effectively carried out by providing consistent teachings,despite varying daily life examples. Similarly, the role of tecahers in shaping the spiritual character of early childhood Keywords: Parents, Teachers,Charakter Spiritual,Early Childhood is effectively implemented within the school environment by consistenly imparting similar teachings through daily life examples.